A era da democracia confusa : a jurisdição constitucional como instrumento de defesa dos direitos fundamentais - Santos, Julia Natália Araújo (2021)
The words seem to have lost their meaning; they are, gradually, being emptied. This is the scenery of the era of the democracy revisited. There is a profession of democratic faith at the same time that, in the practice, their defenders go from ideas and from postulates that go against the basic foundations of democracy. In this reality, we question if the democracy can, then, be anything. Therefore, the concept of democracy revisited formulated by Sartori is rescued, which postulates the existence of the conceptual loss of a theoretical line that represented the democracy. The inquietude about democracy and its confusion era reflects in the constitutional jurisdiction because it is its role to defend the constitution, to examine, under the constitutionality angle, the normative productions, the primordial materialization of democratic regime and to tutelary the fundamental rights. In this context, the research searches for an answer for the following problem: the protection of the fundamental rights by the Federal Supreme Court, constitutionally chosen organ to occupy the apex of the brazilian constitutional jurisdiction, consubstantiates an effective instrument of minimization of perverse effects generated by the era of democracy revisited? Thereby it is seen that the hypothesis that the constitutional jurisdiction, in the tutelage of fundamental rights, has contributed to minimize the effects generated by the era of democracy revisited and its relation with the constitutional jurisdiction, as to examine if the defense of fundamental rights contributes to the minimization of effects given by the era of democracy revisited in the Brazilian context. More specifically, it aims to observe the democracy throughout time; to explore and to concept its revisited era; to study the constitutional jurisdiction and its interface with democracy and the fundamental rights. To do so, it was used the deductive research method, with help of the monographic procedure and the bibliographic, documental and jurisprudential research technique, that was carried out based on the activities report of the FSC. At the end, it was concluded that the constitutional jurisdiction is an effective mechanism to minimize the perverse effects of democracy revisited through the tutelage of fundamental rights. Even though, its activity must be complemented with an education to the democracy because of the lack of democratic culture sedimented within the Brazilian arrangement, beyond the constitutional jurisdiction.